EXPERIMENTAL INVESTIGATION OF SULPHIDE ION PERFORMANCE ON THE GROWTH OF CdZnS NANOPARTICLES - Ibiyemi, A. A.; Olubosede, O.; Awodele, M. K.; Akinrinola, O.; Awodugba, A. O. (FUDMA Journal of Sciences, 2023)
It has been well established in this research work that sulphide ion play a crucial role in chalcogenide semiconductor devices. The impact of sulphide ion content (S2-) on the surface morphology, optical, electrical and micro-structural properties of chemically deposited CdZnS nanoparticles was examined. The nanoparticles were prepared using cadmium sulphate as Cd2+ source, zinc sulphate as Zn2+source and thiourea as S2- source. NH4OH was used as the complexing agent. The thiourea concentration was varied between 0.075 M – 0.580 M while the concentration of ZnSO4, CdSO4 and NH4OH were fixed. EDX was used to confirm the compositional elements of the nanoparticles which are Cd2+, Zn2+, S2- and little content of Si and O2. The SEM analysis revealed good uniformity and densely packed structure. Sulphide-rich nanoparticles exhibit large crystallite size compare to sulphide-poor nanoparticles. XRD indicates hexagonal structure (002) without phase transition.  S2--rich CdZnS revealed less polycrystallinity compare to S2--poor CdZnS samples which exhibit better polycrystallinity. The crystallite size varied between 10 nm to 52 nm. The dislocation density increases from 0.000852 to 0.00242 Line2/m2 and then decreased to 0.000364 Line2/m2. Other microstructural properties such as lattice parameter and micro-strain as well as their relation with grain boundary surface area were also discussed. The best transmittance of about 97% was revealed. The layers deposited with high S2- content showed less percentage transmittance and exhibit narrow energy band gap. The electrical resistivity is decreased while electrical conductivity increases with increasing S2- content. The sheet resistance, charge carrier mobility and charge carrier density
Keywords: CdZnS, nanoparticles, transparent, lattice mismatch, SEM, grain boundary, band gap